Faktor-Faktor yang Memengaruhi Permintaan Buah Jeruk Siam di Kota Surakarta - Devanie Anggun Putri Leksana; Mohamad Harisudin; Refa'ul Khairiyakh (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Increasing public awareness of the importance of fulfilling nutrition and vitamins has resulted in people consuming fruit more massively. One popular fruit is siam citrus because it tends to taste sweet and is readily available on the market, including in Surakarta City. Surakarta City is a potential market for siam citrus because the public consumption of the fruit increases yearly. In contrast, public consumption of siam citrus fluctuates from year to year. The fluctuating level of public consumption means that the demand for siam citrus is also uncertain. Considering this, it is imperative to understand the variables influencing Surakarta City's demand for siam citrus. One hundred respondents who purchased siam citrus from "Pasar Legi, Pasar Gede, Pasar Kadipolo, Pasar Gading, and Pasar Harjodaksino" provided the primary data for this study. The demand function was converted into a multiple linear regression function for data analysis. The analysis's findings indicate that the variables of siam citrus price, mandarin orange price, apple price, mango price, family earnings, number of family members, and taste all affect the siam citrus demand in Surakarta City. The variable price of siam citrus, mandarin orange price, mango price, family earnings, and tastes partially significantly affected the siam citrus demand. Therefore, the demand for siam citrus in Surakarta City was not considerably impacted by the apple price and the number of family members. Taste is the most critical factor influencing the demand for siam citrus.